Borehole depth and regolith aquifer hydraulic characteristics of bedrock types in Kano area, Northern Nigeria - Bala Abdullahi Emmanuel; Eduvie Obada Martins; Byami Jolly (African Journal of Environmental Economics and Management, 2020)
In this study, the performance of regolith aquifers derived from the different bedrock types was examined using information on depth of borehole, depth to the static water level, yield of borehole and drawdown in 259 boreholes covering the different bedrock types. Results show that mean depth of wells varies from about 37 to 48 m in rocks of the Younger Granites and in the migmatite-gneiss complex and schists, respectively. Static water level ranges from about 9 to 18 m in regolith of the Younger Granites and that of the migmatite-gneiss complex and schists, respectively. Yield varies from about 28 to 44 L/min in the migmatite-gniess complex and schist and in the porphyritic granite, respectively. Drawdown varies from about 6 to 9 m in the regolith of the Younger Granite and in that of the migmatite-gneiss complex and schist, respectively. Mean values of specific capacity varies from about 9 to 11 m2/d while transmissivity ranges from about 16 to 20 m2/d. The least values are found with the regolith of the migmatite-gneiss complex and schists while the highest values are found in aquifers of the porphyritic granite. Results further indicate that aquifers derived from rocks of granitic composition tend to exhibit similar hydraulic characteristics. But the poor performance of regolith of the migmatite-gneiss complex and schists (Younger Metasediments) is ascribed to their texture and structure.